THE EFFECT OF LEARNING MEDIA AND LEARNING STYLE TOWARD ENGLISH STUDYING RESULT - Abdul Muhid Murtadho (Journal of English Language and Literature (JELL), 2018)
This research was held to check out the effect of learning media and learning style toward English studying result for the second grade students of the Junior High School. This Research was held at SMP 5 Setu – Bekasi and SMP 12 Tambun - Bekasi. The writer took 165 students as sample for research. The research instrument is the questionnaire of Learning Style and the teaching prosess by using different Learning Media (Multimedia Based and Conventional Based). The methodolgy used by the writer is survey dan experiment which is used treatment anylisi method by level. The type of testing used is Anova Dua Arah. From this research writer found that there is a significant correlation between Learning Media toward English studying result. It was proved by the obtanined of Fo = 11,070 and Sig. = 0,000 < 0,05. There is a significant correlation between Learning Style toward English studying result. It was proved by the obtanined of Fo = 8,982 dan Sig. = 0,000 < 0,05. There is not any significant interaction effect between Learning Media and Learning Style toward English studying result. It was proved by the obtanined of Fo = 0,043 dan Sig. = 0,958 > 0,05